Os experimentos de Griffith no ensino de Biologia: a transposição didática do conceito de transformação nos livros didáticos - Batisteti, Caroline Belotto [UNESP]; Araujo, Elaine Sandra Nicolini Nabuco de [UNESP]; Caluzi, João José [UNESP] (FapUNIFESP (SciELO), 2010)
Griffith's experiments regarding bacterial transformation Pneumococcus are regarded as essential when related to DNA/heredity recognition process. The aim of the current study is to assess the didac tic transposition of the concept of bacterial transformation since the Griffith's descriptions until its current approach on didactic books. We realized that the historical context and the relationship between bacterial transformation and DNA recognition as genetic material are poorly explored. The core of our paper is the historical approach of those exper iments. By considering the wide richness of the knowledge that is ranged on Griffith's experiments, we suggest a didactic transposition concerning bacterial transformation in the learning process, involving an integration of contents.

Os experimentos de Griffith sobre a transformação de bactérias Pneumococcus, são tidos como importantes no processo de reconhecimento da relação DNA/hereditariedade. O presente estudo teve por objetivo analisar a transposição didática do conceito de transformação bacteriana, desde as descrições de Griffith até sua abordagem nos livros didáticos de Biologia. Percebemos que o contexto histórico e a relação entre a trans formação bacteriana e o reconhecimento do DNA como material gené tico são pouco explorados. Considerando a riqueza de conhecimentos, de diferentes áreas, que os experimentos de Griffith abrangem, sugerimos uma transposição didática do conceito de transformação bacteriana que envolva uma integração de conteúdos, tendo como ponto central a abor dagem histórica desses experimentos.
Griffith's experiments on biology teaching: the didactic transposition of the concept of transformation in didactic books
Keywords: Bacteria transformation; Didactic transposition; Biology teaching; Transformação bacteriana; Transposição didática; Ensino de biologia